Muscle activation during forehand and backhand drives in the sport discipline of tennis - Koronas, V.; Koutlianos, N. (Facta Universitatis: Series Physical Education and Sport, 2020)
Tennis is one of the most popular individual sports all over the world. Strength and trained muscles are required for a player in order to achieve a good backhand, forehand, volley or flat stroke. Especially while playing tennis are many kinds of muscles involved, including the lower body muscles, trunk muscles and upper body muscles. The purpose of this review is to present the activated muscles in the basic tennis movements of forehand and backhand and to improve the knowledge about their role in order to help tennis players and coaches to enhance their tennis performance and to reduce risk of injury. To support the present review, data were gathered from library and network databases using keywords such as tennis, muscles, forehand, and backhand for publications between 2015 and 2019. Overall, thirty-five references were detected and used. The literature showed that forehand and backhand drives are strokes that involve muscles not only of the upper limbs but also a series of more complex movements that start with the feet and end with the swinging of the tennis racket. The insight for the action of the muscles in tennis should be utilized in tennis players so as to better understand the muscular function which takes part in specific tennis movements and has a greater performance. In addition, this knowledge is considered strongly beneficial for the coaches and the favourable building of the training process.